LO020: Obstacle course runs: review of acquired injuries and illnesses at a series of Canadian events (RACE). (2nd June 2016) - Hawley, A.; Hanel, E.
Abstract : Introduction: The growing popularity of obstacle course runs (OCRs) has led to significant concerns regarding their safety. The influx of injuries and illnesses in rural areas where OCRs are often held can impose a large burden on first responders, Emergency Medical Services (EMS) and local Emergency Departments. Literature concerning these events is minimal and mostly consists of media reports. Recognizing the lack of epidemiologic data, we sought to accurately determine the patterns and frequency of injuries and illnesses that occur at OCRs, the treatments required, and what proportion require further medical care or transfer to hospital.Methods: Data were extracted from medical charts completed for all patients presenting to the on-site medical team at OCR events across Canada from May to August, 2015. Frequency and patterns of injuries and illnesses were determined as well as treatments and disposition. There were 45 285 OCR participants in 8 events. There were 572 total patient contacts and 557 patients were included in the study. 15 patients were excluded because they were not race participants.Results: Less than 2% of participants at any event required on-site medical care. 11 patients (1.97%) required transfer to hospital by EMS. The majority of injuries were musculoskeletal in nature (74.71%). 495 patients (88.87%) returned to the event with no need for further medical care. The majority of treatments could be provided with first aid training and basic medical equipment.Conclusion: Injury and illness rates at this series of OCRs was similar to other mass gathering events. Injuries were mostly musculoskeletal in nature and required minor treatment. Having a medical team on site likely reduced local hospital and EMS volume from these events. This study raises the question of whether having a physician on site at OCRs could significantly reduce the number of patients advised to seek further medical care or the number of ambulance transfers. Prospective research is needed in order to develop plans for more appropriate resources, safety protocols, and medical staffing, thereby improving patient care and reducing the burden on local EMS and rural hospitals.